The land–sea interface: A source of high‐quality phytoplankton to support secondary production. (15th September 2017) - Winder, Monika; Carstensen, Jacob; Galloway, Aaron W. E.; Jakobsen, Hans H.; Cloern, James E.
Abstract: Coastal‐estuarine systems are among the most productive marine ecosystems and their special role in producing harvestable fish and shellfish has been attributed to high primary production fueled by nutrient runoff from land and efficient trophic transfer. Here we ask if phytoplankton species composition and their food quality based on the percentage of long‐chain essential fatty acids (LCEFA) is another factor contributing to high secondary production in these ecosystems. We used long‐term measurements of major phytoplankton taxonomic groups and estimated their content of LCEFA along the salinity gradient in coastal‐estuarine ecosystems, with emphasis on Chesapeake Bay and the Baltic Sea, and an oceanic transect. Our data show that cyanobacteria with low nutritional quality often dominate at low‐salinity regions, while intermediate to higher salinity regions produce diatoms and dinoflagellates that have a higher content of LCEFA and are thus a higher‐quality food resource for consumers. Higher salinity regions have less pronounced seasonal changes in the percentage of phytoplankton LCEFA compared to low salinity regions, providing a stable supply of nutritious phytoplankton to consumers. The phytoplankton LCEFA content is similarly high in coastal upwelling systems and it decreases further offshore in oligotrophic oceanic regions dominated by picophytoplankton. Our results from a broad range of coastal‐ecosystem types show that ecosystems at the land‐sea interface provide a valuable service by producing phytoplankton enriched in the biochemicals essential for consumers. High primary production, coupled with high quality of that production, explain why the production of fish and shellfish is high where land and sea meet.